2020
DOI: 10.1002/ajb2.1568
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid capture of 964 nuclear genes resolves evolutionary relationships in the mimosoid legumes and reveals the polytomous origins of a large pantropical radiation

Abstract: The field of molecular plant phylogenetics has had tremendous impacts on botanical studies and taxonomic classification, macroevolution and biogeography, ever since the pioneering studies of Chase et al. (1993) based on DNA sequence data. While those early studies used just a single locus, the plastid gene rbcL, modern studies often employ hundreds to several thousands of genes to infer phylogenetic relationships (e.g.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
217
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(334 citation statements)
references
References 101 publications
25
217
2
1
Order By: Relevance
“…In mimosoids, our results indicate that the 3 tribes Mimoseae (Luckow et al, 2003), Ingeae, and Acacieae (including the genera Acacia s.s., Senegalia, and Vachellia) are all nonmonophyletic (Figure 2), generally consistent with previous studies (Chappill and Maslin, 1995;K€ ass and Wink, 1996;Luckow et al, 2003;Pertea et al, 2003;Kyalangalilwa et al, 2013;LPWG, 2017;Zhang et al, 2020b;Koenen et al, 2020). The analyses here yielded a largely consistent and wellresolved topology that divides the sampled mimosoids into 17 clades.…”
Section: Highly Supported Relationships In Caesalpinioideaesupporting
confidence: 89%
“…In mimosoids, our results indicate that the 3 tribes Mimoseae (Luckow et al, 2003), Ingeae, and Acacieae (including the genera Acacia s.s., Senegalia, and Vachellia) are all nonmonophyletic (Figure 2), generally consistent with previous studies (Chappill and Maslin, 1995;K€ ass and Wink, 1996;Luckow et al, 2003;Pertea et al, 2003;Kyalangalilwa et al, 2013;LPWG, 2017;Zhang et al, 2020b;Koenen et al, 2020). The analyses here yielded a largely consistent and wellresolved topology that divides the sampled mimosoids into 17 clades.…”
Section: Highly Supported Relationships In Caesalpinioideaesupporting
confidence: 89%
“…2016;Ferm & al. 2019;Koenen & al. 2020a), or had a broader focus in the Fabaceae or the mimosoid clade (e.g., Luckow & al.…”
Section: Introductionmentioning
confidence: 99%
“…
We investigated generic relationships in the ingoid clade (Fabaceae) (sensu Koenen & al. 2020a), with main focus on genera with a taxonomic history in Calliandra s.l.
…”
mentioning
confidence: 99%
“…The results indicate that the Citrus radiation is statistically indistinguishable from a series of simultaneous speciation events, and thus that the true Citrus phylogeny might be better explained as a multifurcating tree at the origin of the crown. Previous studies have revealed the existence of hard polytomies in the base of other plant radiations, where the increase of the amount of data analyzed fails to converge into a unique solution (Carlsen et al, 2018;Koenen et al, 2020;Larson et al, 2020). Given the drastic change in the climatic conditions that occurred in South East Asia in the Late Miocene (Herbert et al, 2016;Holbourn et al, 2018;Tanner et al, 2020), it is hypothesized that the basal polytomy at the Citrus crown might represent the true speciation history of the genus, which would in turn explain the historical inconsistencies regarding its phylogeny (Nicolosi et al, 2000;Ramadugu et al, 2013;Oueslati et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The observation that the nonmatching tree topologies arise from the different branching order of these nodes indicate that very likely several Citrus species emerged almost simultaneously, in a short period of time in an evolutionary timescale. In previous studies, some authors have argued that rapid radiations are accompanied by "hard" polytomies, implying that the true evolutionary history of the clade tree involves a polytomy, produced by concurrent speciation events that generate a truly multifurcating tree (Suh et al, 2015;Dillenberger and Kadereit, 2017;Koenen et al, 2020). In hard polytomies, strictly bifurcating trees fail to capture the underlying evolutionary history of that clade, producing spurious topologies (Bapteste et al, 2013;Hahn and Nakhleh, 2016).…”
Section: A Rapid Radiation At the Base Of The Genus Citrusmentioning
confidence: 99%